The diffusion of activity-based costing system's adoption in the Malaysian manufacturing firms through technology acceptance model - Al-Taria, Nashwan Talal Saadallah (2020)
Globally, the adoption of Activity-Based Costing (ABC) system is still low. The low adoption might be due to several organizational, technological and other factors. Hence, this study investigates the factors that affect the adoption behavior of ABC system from the organizational context. Based on Technology Acceptance Model (TAM) and Diffusion of Innovation (DOI) theory, seven hypotheses were formulated to accomplish this target. A questionnaire survey was used for collecting data from the managerial level respondents in the Malaysian manufacturing firms. A total of 145 usable questionnaires were received, the collected data were exposed to tests of factor analysis and multiple regression using Smart Partial Least Square (PLS) software. The findings revealed that organizational culture has influential role on firms’ intention to adopt ABC system, whereas management support has not, Furthermore, the intention to adopt ABC system significantly influence its actual adoption, whilst both perceived benefits and perceived attributes of ABC system have a mediation role amongst management support, organizational culture and the intention to adopt ABC system. These findings imply that the adoption of ABC system in Malaysian manufacturing firms is explained by the perception of its attributes and its benefits; and they are important in the adoption behavior of Malaysian organizational culture. However, management support requires perceived attributes and benefits of ABC system to be exerted. This study adds to the body of knowledge by giving more explanations on ABC adoption behavior and providing further insight for the factors that assist and hinder the adoption of ABC system in the manufacturing sector. In conclusion, the research fills the gap in ABC system acceptance literature in general and in Malaysian manufacturing firms in particular. More importantly, this research has opened up opportunities for further investigation into ABC system acceptance in other developing countries, and worldwide.